Economic efficiency of two baling systems for sugarcane straw - Lemos, S. V. [UNESP]; Denadai, M. S. [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP]; Bueno, Osmar de Carvalho [UNESP]; Takitane, Izabel Cristina [UNESP] (Elsevier B.V., 2014)
In recent years, harvesting process of sugarcane is changing itself, passing through semi-mechanized for mechanized system, who, currently predominate in Sao Paulo state, Brazil. Mechanized harvesting consists in a sequence of operations which includes cutting the pointer and chopping the stalk. The straw is a harvesting residue, and it stays in the ground, piling up above soil, with a possible prejudice for crop yield. An economic way to retract this straw is using mechanized processing for bailing it, involving hay balers, which are imported to Brazil and their use require regularly field conditions of work. Those balers could produce square or round bales, which can be sold to energy generation. This study aims to estimate economic efficiency indicators of round and square systems for sugarcane straw, establishing a relationship between baling costs and the incoming generated from those bales. Based on data set, round baling system was 26% more efficient than square baling system, and that round baler has a lower purchase price and a higher compress ratio of biomass, allowing a greater potential for power generation, turning it a more advantageous in a possible marketing for bales produced. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Machine costs; Round and square balers; Techno-economics